Two Conservative Difference Schemes for Rosenau-Kawahara Equation - Jinsong Hu; Youcai Xu; Bing Hu; Xiaoping Xie (Advances in Mathematical Physics)
Two conservative finite difference schemes for the numerical solution of the initialboundary value problem of Rosenau-Kawahara equation are proposed. The difference schemes simulate two conservative quantities of the problem well. The existence and uniqueness of the difference solution are proved. It is shown that the finite difference schemes are of second-order convergence and unconditionally stable. Numerical experiments verify the theoretical results.